Pengaruh Padat Tebar dan Salinitas yang Berbeda terhadap Pertumbuhan dan Kelangsungan Hidup Post Larva Udang Vannamei (Litopenaeus Vannamei) - Muhammad Habibi Yusuf; Nurjanah Nurjanah; Sutaman Sutaman (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2026)
The white shrimp (Litopenaeus vannamei) is one of the popular marine shrimp species in aquaculture due to its adaptability to various environmental conditions, including a wide range of salinity, and its omnivorous feeding behavior. This study aims to determine the effect of different combinations of stocking density and salinity on the growth rate and post larval survival of vaname shrimp (Litopenaeus vannamei). The research was conducted using factorial planning based on two factors namely stocking density (3, 6, and 9ekor/L) and salinity (15 ppt and 25 ppt). Parameters measured included daily growth rate, absolute weight, survival rate, feed utilization efficiency, and feed conversion ratio (FCR). Water quality observations were also made during the study period including temperature, pH, dissolved oxygen, salinity, and total ammonia. The results showed that the combination of stocking density of 3 fish/L with salinity of 25 ppt gave the best results with a daily growth rate of 0,00664 gram and a survival rate of 86%. This treatment also produced the best feed utilization efficiency of 0.87 and the best FCR value of 1.27, indicating the most efficient use of feed. Water quality parameters during the study were within the appropriate range to support the growth of vanamei shrimp.